2018
DOI: 10.1038/s41598-018-29289-7
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of known and novel microRNAs in strawberry fruits induced by Botrytis cinerea

Abstract: MicroRNAs are endogenous small non-coding RNAs that negatively regulate mRNAs, mainly at the post-transcriptional level, and play an important role in resistance response of plants. To date, there are few reports on resistance response of strawberry miRNAs to pathogens. In this study, using high-throughput sequencing, 134 conserved and 35 novel miRNAs were identified in six libraries within the treatment of Botrytis cinerea. A total 497 potential target genes were predicted using Fragaria vesca genome. Most of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 61 publications
(67 reference statements)
2
5
0
Order By: Relevance
“…Although little attention has been focused on the calcium signaling pathway genes in the interaction between strawberry and B . cinerea , our knowledge on the Ca 2+ dependent-immunity mechanisms advanced recently (Liang et al, 2018 ; Xiong et al, 2018 ; Haile et al, 2019 ). Considering the model plant Arabidopsis as an example, active BOTRYTIS-INDUCED KINASE1 (BIK1) and CPKs phosphorylate Ca 2+ -bound RBOHD to boost ROS production.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although little attention has been focused on the calcium signaling pathway genes in the interaction between strawberry and B . cinerea , our knowledge on the Ca 2+ dependent-immunity mechanisms advanced recently (Liang et al, 2018 ; Xiong et al, 2018 ; Haile et al, 2019 ). Considering the model plant Arabidopsis as an example, active BOTRYTIS-INDUCED KINASE1 (BIK1) and CPKs phosphorylate Ca 2+ -bound RBOHD to boost ROS production.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that B. cinerea inoculum primarily enters the strawberry flower organs; the infected petals, stamens, and calyxes and then facilitate primary infection in fruits (Petrasch et al, 2019 ). The previous studies have focused primarily on the interaction of on B. cinerea with strawberry fruit (Liang et al, 2018 ; Xiong et al, 2018 ; Haile et al, 2019 ) while paying little attention to its interaction with the flower.…”
Section: Introductionmentioning
confidence: 99%
“…B. cinerea can suppress the expression of plant defence responses by hijacking the host sRNA regulatory pathways (Weiberg et al , ). In strawberry fruits, B. cinerea infections can alter the expression of microRNAs involved in the regulation of defence genes, including the plant intracellular Ras group‐related LRR protein 9‐like gene (Liang et al ). Interestingly, B. cinerea can also take up plant sRNAs during its interaction with the host.…”
Section: Mechanisms Of Defence and Avoidance Against Botrytis Cinereamentioning
confidence: 99%
“…•Botrytis cinerea Species Newly expanding young leaves may be infected by this pathogen but don't illustrate symptoms because the fungus remains dormant in these tissues (Liang et al, 2018). When the leaves are mature and beginning to senesce and decline, B. cinerea can become active and construct the characteristic grey, velvety growth on the dead parts of the leaf (Williamson et al, 2007).…”
Section: •Eukaryota Domainmentioning
confidence: 99%